Requirements For the Professional Competence of Physical Culture Students (Journal of Pedagogical Inventions and Practices, 2023)
The problem of increasing the level of professional competence of a student who has the ability to think freely and actively, model the educational process, develop and implement new ideas and technologies of teaching and upbringing is considered urgent in modern socio-economic conditions.